2018
DOI: 10.1097/gco.0000000000000452
|View full text |Cite
|
Sign up to set email alerts
|

What is new in the management of poor ovarian response in IVF?

Abstract: Many strategies have been proposed to manage poor responder patients, however, a consensus upon which is the most beneficial has not been yet reached. DuoStim is the most promising approach to increase the number of oocytes collected in a single ovarian cycle; however, more embryological and clinical data is required, as well as an analysis of its cost-effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 85 publications
0
68
0
1
Order By: Relevance
“…However, the IVA method has been considered equivocal regarding its efficacy and safety whereas in vitro studies have suggested that activation by pharmacological methods may negatively affect oocytes' quality (118)(119)(120)(121). Indeed, it has been suggested that IVA combined with PI3K/Akt and Hippo signaling pathways before ovarian slices auto-transplantation may bear major negative consequences on follicle health (118,(122)(123)(124)(125).…”
Section: In Vitro Activation Of Folliclesmentioning
confidence: 99%
“…However, the IVA method has been considered equivocal regarding its efficacy and safety whereas in vitro studies have suggested that activation by pharmacological methods may negatively affect oocytes' quality (118)(119)(120)(121). Indeed, it has been suggested that IVA combined with PI3K/Akt and Hippo signaling pathways before ovarian slices auto-transplantation may bear major negative consequences on follicle health (118,(122)(123)(124)(125).…”
Section: In Vitro Activation Of Folliclesmentioning
confidence: 99%
“…DuoStim, combining two consecutive stimulations spanning a 5-day interval, has been put forward as a valuable opportunity also for the management of poor-prognosis patients such as women with reduced ovarian reserve and/or advanced maternal age. The aim then is to maximize the number of oocytes retrieved in a single ovarian cycle, or to rescue patients in whom no oocytes were retrieved or competent embryos were not produced after conventional FPS (27)(28)(29)(30). For these thorny populations of patients, there is insufficient evidence to outline an ideal management since, regardless of the COS protocol adopted, consistently low live birth rates have been reported.…”
Section: When Is Duostim Indicated?mentioning
confidence: 99%
“…Moreover, the total amount of gonadotrophins used is lower when COS is performed with r-FSH compared with HMG (66,67). All these aspects must be considered when we treat poor-prognosis patients where even a single oocyte can make a huge difference in terms of cumulative results and cost-benefit (28).…”
Section: Weaknesses Risks and Concerns Related To Duostimmentioning
confidence: 99%
“…The population of patients that fulfilled these eligibility criteria was divided into four different patterns: (1) age ≥40 years and abnormal ORT, (2) age ≥40 years, abnormal ORT and one previous poor response to stimulation, (3) age ≥40 years and one previous poor response, (4) abnormal ORT and one previous poor response to stimulation (11).…”
Section: Bologna Criteria Patternsmentioning
confidence: 99%
“…The occurrence of poor ovarian response amongst patients undergoing ovarian stimulation for in vitro fertilization (IVF) ranges from 9 to 24%, meaning that almost one in four patients harbors a poor reproductive prognosis (1)(2)(3)(4). This category of patients commonly referred to as poor responders (PORs), remains a challenge for the fertility expert, as studies up to now have failed to identify a therapeutic approach that can modify or improve their fertility outcomes (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%